A case study of a collaborative allied health and nursing crisis response. Issue 5 (2nd September 2020) - Hales, Pippa; White, Anne; Eden, Allaina; Hurst, Rhys; Moore, Siobhan; Riotto, Cheryl; Achour, Nebil
ABSTRACT: The COVID-19 pandemic was declared by the World Health Organization on 11 March 2020. The rapid spread of SARS-CoV-2 required an equally rapid response from health-care organizations to find innovative ways to utilize the existing workforce to care for people with COVID-19. Using an evaluative case study, a unique insight into the collaborative allied health and nursing professions' response to COVID-19 at a specialist cardiothoracic hospital in the United Kingdom is presented. The aim of the case study was to evaluate how an interprofessional workforce from the wider organization could be supported to work in critical care as part of a crisis response. In identifying the key enablers to setting up an interprofessional Essential Care Team and learning from the lived experiences of those involved, t his case study has demonstrated that, in supported, interprofessional teams the wider organizational workforce can be facilitated to effectively and safely provide critical care services. The lessons learned from this study will support future pandemic responses and aid the identification of further opportunities for interprofessional learning and practice. Ultimately, the study highlights that by identifying and investing in the key enablers, health-care organizations can be better prepared to respond to a global crisis.